Barriers to creative destruction: Large firms and nonproductive strategies - Salomé Baslandze (Federal Reserve Bank of Atlanta, 2021)
This working paper reviews recent empirical evidence on large firms and nonproductive strategies that hinder creative destruction and reallocation. The focus is on three types of nonproductive strategies: political connections, nonproductive patenting, and anticompetitive acquisitions. Across different contexts using granular micro data sets, we overwhelmingly see that as firms gain market share, they increasingly rely on nonproductive strategies but reduce their productive, innovation-based strategies. I also discuss theoretical channels, aggregate implications, and potentials for some policies.
Keywords: O3; O4; 330; creative destruction; innovation; growth; patents; political connections; firm dynamics